1991
DOI: 10.3758/bf03198498
|View full text |Cite
|
Sign up to set email alerts
|

Skilled memory in expert figure skaters

Abstract: The present studies extend skilled-memory theory to a domain involving the performance of motor sequences. Skilled figure skaters were better able than their less skilled counterparts to perform short skating sequences that were choreographed, rather than randomly constructed. Expert skaters encoded sequences for performance very differently from the way in which they encoded sequences that were verbally presented for verbal recall. Tasks interpolated between sequence and recall showed no significant influence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
1
4

Year Published

1992
1992
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 15 publications
1
28
1
4
Order By: Relevance
“…These findings have since been replicated in many other domains, including bridge (Charness, 1979), figure skating (Deakin & Allard, 1991), and schematic diagrams (Egan & Schwartz, 1979). The general conclusion that emerges from this body of research is that memory-recall performance on meaningful stimuli is correlated with domain expertise (see Vicente, 1988, for a review).…”
mentioning
confidence: 76%
“…These findings have since been replicated in many other domains, including bridge (Charness, 1979), figure skating (Deakin & Allard, 1991), and schematic diagrams (Egan & Schwartz, 1979). The general conclusion that emerges from this body of research is that memory-recall performance on meaningful stimuli is correlated with domain expertise (see Vicente, 1988, for a review).…”
mentioning
confidence: 76%
“…Furthermore, the theory of area-restricted cognition would suggest that certain kinds of thinking are associated with certain kinds of multidimensional foraging strategies. Evidence supporting skilled memory theory shows that professionals are more likely to remember items configured according to the rules of their domain, as in chess (Chase & Simon, 1973) and figure skating choreography (Deakin & Allard, 1991). Some domains may be inherently more flexible than others, which may call for more or less flexible navigation (e.g., jazz vs. classical musicians).…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
“…Mnemonic ability for representative stimuli from a domain of expertise has been seen as essential for acquisition of that expertise, and studies have shown that memory for images can be augmented by expertise in the field to which the images relate. Master chess, bridge, or sports players and computer programmers have superior ability compared to nonexperts in memorizing meaningful material from their general domains of expertise, [5][6][7][8][9][10] but not for randomly rearranged versions of those stimuli. This memory seems to be linked to recognition of specific patterns.…”
Section: Introductionmentioning
confidence: 99%